2022
DOI: 10.3389/fphar.2022.845600
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroquercetin Attenuates Silica-Induced Pulmonary Fibrosis by Inhibiting Ferroptosis Signaling Pathway

Abstract: Silicosis is a fatal occupational lung disease which currently has no effective treatment. Dihydroquercetin (DHQ) is a flavonoid compound known for its anti-inflammatory, anti-oxidant and anti-cancer bioactivity. However, whether DHQ protects against silica-induced lung fibrosis remains unknown. Therefore, we aimed to investigate the effect of DHQ on silica-induced lung fibrosis and the underlying molecular mechanism in vivo and in vitro. Our results demonstrated that DHQ treatment markedly attenuated SiO2-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 52 publications
(81 reference statements)
0
22
0
Order By: Relevance
“…In recent years, researchers' interests have increasingly focused on the molecular mechanisms of ferroptosis and ferritinophagy, alongside the prevention and treatment of various related diseases. Relevant studies reported that ferroptosis is associated with various lung diseases, including acute lung injury, pulmonary fibrosis, COPD, pulmonary heart disease, and lung cancer (Brown et al, 2019; Yatmark et al, 2015; Yoshida et al, 2019; L. Yuan et al, 2022). According to previous reported, whole cigarette smoke condensates induced ferroptosis in bronchial epithelial cells via endoplasmic reticulum stress and mitochondrial dynamic cause by induction of hypoxic conditions (Park et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, researchers' interests have increasingly focused on the molecular mechanisms of ferroptosis and ferritinophagy, alongside the prevention and treatment of various related diseases. Relevant studies reported that ferroptosis is associated with various lung diseases, including acute lung injury, pulmonary fibrosis, COPD, pulmonary heart disease, and lung cancer (Brown et al, 2019; Yatmark et al, 2015; Yoshida et al, 2019; L. Yuan et al, 2022). According to previous reported, whole cigarette smoke condensates induced ferroptosis in bronchial epithelial cells via endoplasmic reticulum stress and mitochondrial dynamic cause by induction of hypoxic conditions (Park et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This process eventually triggers ferroptosis. Although the relationship between ferroptosis and beryllium disease is not well defined, its role in lung diseases has been established, including acute lung injury, pulmonary fibrosis, chronic obstructive pulmonary disease (COPD), pulmonary heart disease, and lung cancer (Brown et al, 2019; Xu et al, 2021; Yoshida et al, 2019; L. Yuan et al, 2022). For example, whole cigarette smoke condensates induced ferroptosis in bronchial epithelial cells through endoplasmic reticulum stress and the hypoxic‐induced disturbance of mitochondrial dynamic homeostasis (Park et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Dihydroquercetin, a plant flavanonol isolated from yew, protected against SiO 2 -induced lung fibrosis in C57BL/6 mice. 133 Mechanistically, dihydroquercetin inhibited ferritinophagy by reducing the expression of microtubule-associated protein 1A/1B light chain 3 (LC3), thereby alleviating iron accumulation and lipid peroxidation in bronchial epithelial cells. Moreover, glabridin from licorice could ameliorate glucose metabolism and renal injury in diabetic rats by inhibiting ferroptosis, which was associated with the decreased expression of TFR and the increased expression of SLC3A2, SLC7A11, and GPX4 in renal tissues.…”
Section: Flavanonesmentioning
confidence: 99%
“…Further studies confirmed that silibinin could suppress the enzymatic activity of ACSL4 by directly binding to it, which inhibited ferroptosis in hepatocytes and thus exerted hepatoprotective effects. Dihydroquercetin, a plant flavanonol isolated from yew, protected against SiO 2 -induced lung fibrosis in C57BL/6 mice . Mechanistically, dihydroquercetin inhibited ferritinophagy by reducing the expression of microtubule-associated protein 1 A /1B light chain 3 (LC3), thereby alleviating iron accumulation and lipid peroxidation in bronchial epithelial cells.…”
Section: Natural Flavonoids Targeting Ferroptosismentioning
confidence: 99%
“…A study reported that ferroptosis inhibitors effectively circumvent the toxicity of paraquat, and ferroptotic death may have a considerable contribution to paraquat-mediated pathological changes in lung tissue [100]. According to a recently study, dihydroquercetin has significant efficacy against silica-induced pulmonary fibrosis, ameliorating fibrotic manifestations by 10 Oxidative Medicine and Cellular Longevity inhibiting ferritinophagy-mediated ferroptosis in human bronchial epithelial cells [101]. damage to ATII cells is involved in the process of lung fibrosis.…”
Section: Ferroptosis and Lung Fibrosismentioning
confidence: 99%